Open Innovation: Implications for Corporate Strategies, Government Policy and International R&D Spillovers - Jean Guinet; Dirk Meissner (Foresight and STI Governance)
The paper analyzes the contribution of public policy to the open innovation process. Innovation processes are dynamic and global. Actors must adapt their strategies to new contexts, including the increasingly knowledge-based global competition. They must reconcile the need for speed in commercial exploitation of new products in order to ensure continuous investments with long lead-time in the development of radical innovation capabilities. For the world leaders in their industries, suppliers are becoming ever more important not only as sources but also contributors to innovation, which requires complementary and open interaction between the private sector and public research. The trend is toward open innovation processes, that make possible the overcoming of geographic, institutional and disciplinary barriers.